Design and Evaluation of Solar PV On-Grid Connected Power Plant Using PVsyst Software in Bani Walid Hospital / Libya - Osama Moftah AlMakhzzom; Abdussalam Ali Ahmed (African Journal of Advanced Pure and Applied Sciences, 2023)
In recent years, the production of electricity from renewable energy sources (RES) has increased due to the multiple benefits of RES: non-polluting, free of raw materials, ecologically benign, and cost-effective. In order to enhance output and efficiency, kinds of RES are associated with geographical places where they are abundant. This paper presents the design and simulation of a solar PV grid-connected electricity generation system in Bani Walid hospital. It also represents the technical and annual performance of the solar PV system. The design is validated and simulated by using PVsyst software in order to determine the optimum size, the specifications of the PV grid-connected system, and the electrical power generation. The amount of electricity that a solar PV plant generates is 7 MW. This amount could be used to reduce the load of Bani Walid city and help to minimize the annual electricity bill of Bani Walid hospital. This work can serve as a successful example of clean energy producers and a business model that encourages individuals and government utilities to utilize solar photovoltaic (PV) technology for electricity demand fulfilment and lucrative investment.